A single-cysteine mutant and chimeras of essential Leishmania Erv can complement the loss of Erv1 but not of Mia40 in yeast - Specht, Sandra Katharina; Liedgens, Linda; Duarte, Margarida; Stiegler, Alexandra; Wirth, Ulrike; Eberhardt, Maike; Tomás, Ana; Hell, Kai; Deponte, Marcel (Redox Biology, 2017)
Mia40/CHCHD4 and Erv1/ALR are essential for oxidative protein folding in the mitochondrial intermembrane space of yeast and mammals. In contrast, many protists, including important apicomplexan and kinetoplastid parasites, lack Mia40. Furthermore, the Erv homolog of the model parasite Leishmania tarentolae (LtErv) was shown to be incompatible with Saccharomyces cerevisiae Mia40 (ScMia40). Here we addressed structure-function relationships of ScErv1 and LtErv as well as their compatibility with the oxidative protein folding system in yeast using chimeric, truncated, and mutant Erv constructs. Chimeras between the N-terminal arm of ScErv1 and a variety of truncated LtErv constructs were able to rescue yeast cells that lack ScErv1. Yeast cells were also viable when only a single cysteine residue was replaced in LtErvC17S. Thus, the presence and position of the C-terminal arm and the kinetoplastida-specific second (KISS) domain of LtErv did not interfere with its functionality in the yeast system, whereas a relatively conserved cysteine residue before the flavodomain rendered LtErv incompatible with ScMia40. The question whether parasite Erv homologs might also exert the function of Mia40 was addressed in another set of complementation assays. However, neither the KISS domain nor other truncated or mutant LtErv constructs were able to rescue yeast cells that lack ScMia40. The general relevance of Erv and its candidate substrate small Tim1 was analyzed for the related parasite L. infantum. Repeated unsuccessful knockout attempts suggest that both genes are essential in this human pathogen and underline the potential of mitochondrial protein import pathways for future intervention strategies.